A criminalidade feminina no Piauí: as representações da criminosa nos jornais e processos criminais, no período de 1981 a 1999 - Araujo, Lucélia Nárjera de (Universidade do Vale do Rio dos Sinos, 2024)
This study assesses female criminality in Piauí State between 1981 and 1999. More specifically, we address the social and legal representations of women and their criminal charges. We seek to understand how gender and moral conditioning, based on social roles, are triggered to accuse or defend defendants. The body of this research is based on crime news published in the newspapers “O Dia” and “O Estado” and an analysis of the criminal proceedings. In addition to these sources, bibliographical and statistical data are added, approached using the methodology of discourse analysis and Italian microhistory, following the suggestions of Giovanni Levi (2020; 2011) and Carlo Ginzburg (1989). We used theoretical frameworks from Michel Foucault (2005), Pierre Bourdieu (2011), Roger Chartier (2001), and Joan Scott (1995). Through these lenses, it was observed that women committed various crimes, for diverse reasons, acting with cunning, courage, insensitivity, boldness, and cruelty. In the analyzedsources, women were represented with the stereotypes of “murderer”, “criminal”, and “dangerous”. Through criminal proceedings, it was verified that the gender category permeates legal practices, mentioned in the speeches elaborated to convict or acquit defendants, based on the representation of social roles conceived for men and women. Through a multidisciplinary dialogue between History, Sociology, and Law, the present research indicates that legal agents resorted to the moral conduct of defendants to formulate their defenses or accusations.

La presente analiza la criminalidad femenina en Piauí entre los años 1981 y 1999. Para eso abordamos las representaciones sociales y jurídicas sobre las mujeres y sus acciones criminales. Buscamos aprender cómo las condiciones del género y la moral, basado en el papel social activado a fin de acusar o defender a las reas. La documental obtenida en la investigación está compuesto por publicaciones en los diarios "O Dia" y "O Estado" y análisis de casos penales. A estas se suman datos bibliográficos y estatísticos, analizados por la metodología del análisis del discurso y la micro-historia italiana, siguiendo las sugerencias de Giovanni Levi (2020,2011) y Carlo Ginzburg (1989). Utilizamos referências teóricas de Michel Foucault (2005, Pierre Bourdieu (2011), Roger Chartier (2001) y Joan Scott (1995). A través de la perspectiva adoptada, se observa que las mujeres cometieron crimenes diversos por motivos vários, actuando con astucia, coraje, insensibilidad, crueldad y osadía. Fueron representadas con los estereotipos de 'asesina', 'criminosa', 'peligrosa'. Por medio del curso procesal penal se corroboró que la categoría de género supera las prácticas jurídicas, referidas en los discursos elaborados para condenar o absolver a las acusadas. Basado en la representación de papeles sociales creados al masculino y femenino. A través de un diálogo multidisciplinario entre Historia, Sociología y Derecho, la encuesta muestra que los letrados analizaron la conducta moral de las imputadas para formular sus defensas o acusaciones.
Keywords: Crime; Criminalidade feminina; Mulheres; Gênero; Violência; Female crime; Women; Genre; Violence; Crimen; Criminalidad femenina; Mujer; Género; Violencia; ACCNPQ::Ciências Humanas::História